2014
DOI: 10.1002/cne.23547
|View full text |Cite
|
Sign up to set email alerts
|

The role of voltage‐gated calcium channels in neurotransmitter phenotype specification: Coexpression and functional analysis in Xenopus laevis

Abstract: Calcium activity has been implicated in many neurodevelopmental events, including the specification of neurotransmitter phenotypes. Higher levels of calcium activity lead to an increased number of inhibitory neural phenotypes, while lower levels of calcium activity lead to excitatory neural phenotypes. Voltage-gated calcium channels (VGCCs) allow for rapid calcium entry and are expressed during early neural stages, making them likely regulators of activity-dependent neurotransmitter phenotype specification. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Investigation of the role of calcium during these events could provide additional insight due to observed antagonism of calcium channels by MeHg (Yuan et al 2005), and the importance of calcium in cell migration and neural phenotype specification. Recently, frequent calcium spiking in neural progenitors, suggested to be inhibited by MeHg (Fahrion et al 2012; Kong et al 2013), has been implicated to lead to a GABAergic phenotype (Lewis et al 2014; Marek et al 2010), providing an additional possible mechanism for the enhanced downregulation of inhibitory neuronal populations by MeHg and the resulting neurological sensory and motor defects.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the role of calcium during these events could provide additional insight due to observed antagonism of calcium channels by MeHg (Yuan et al 2005), and the importance of calcium in cell migration and neural phenotype specification. Recently, frequent calcium spiking in neural progenitors, suggested to be inhibited by MeHg (Fahrion et al 2012; Kong et al 2013), has been implicated to lead to a GABAergic phenotype (Lewis et al 2014; Marek et al 2010), providing an additional possible mechanism for the enhanced downregulation of inhibitory neuronal populations by MeHg and the resulting neurological sensory and motor defects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has also been observed that calcium spike activity mediates dopaminergic and GABAergic specification within the ventral suprachiasmatic nucleus of Xenopus laevis. This specification is seen to be activity-dependent and is prevented by inhibiting calcium transients ( Marek et al, 2010 , Lewis et al, 2014 ). Thus, it is not surprising that subtle alterations in calcium channel function can alter neuronal connectivity, influencing cognitive functions later in life.…”
Section: Involvement Of Voltage-gated Calcium Channels In Early Brainmentioning
confidence: 99%
“…The lower expression of GABA and xGAD67 transcripts was rescued in the absence of extracellular calcium by reimposition of intracellular calcium transients at the frequency normally generated in cultured neurons (Figure 5) (Gu and Spitzer, 1995; Watt et al, 2000). In more recent work, blockade of calcium spikes increased the number of neurons expressing xVGluT1 and decreased the number of neurons expressing xGAD67 transcripts; enhancing calcium spiking reduced the number of neurons expressing xVGluT1 without detectable effect on the number of neurons expressing xGAD67 (Lewis et al, 2014). …”
Section: Transmitter Switching During Development: Cns Neuronsmentioning
confidence: 99%